2013
DOI: 10.1007/s13744-013-0164-y
|View full text |Cite
|
Sign up to set email alerts
|

Species Diversity and Temporal Variation of the Orchid-Bee Fauna (Hymenoptera, Apidae) in a Conservation Gradient of a Rocky Field Area in the Espinhaço Range, State of Minas Gerais, Southeastern Brazil

Abstract: This study investigated the orchid-bee community in a conservation gradient of the high-altitude rocky fields in the state of Minas Gerais, Brazil. Sampling was performed at two sites with different anthropic influences: a disturbed area (DA), with exotic plant species, and a preserved area (PA). From September 2009 through February 2011, males of euglossine bees were sampled using aromatic bait-traps. We collected a total of 819 specimens belonging to 11 species and three genera: Euglossa Latreille, Eulaema L… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
13
2
3

Year Published

2014
2014
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(20 citation statements)
references
References 44 publications
2
13
2
3
Order By: Relevance
“…In particular, the assembly of bee pollinator communities is strongly influenced by climatic factors as well as variation in food resource availability, which in turn also fluctuates in response to climatic variables (Ramirez et al, 2015). As reported by some authors (Rebêlo & Garófalo, 1991;Silveira et al, 2011;Andrade-Silva et al, 2012;Viotti et al, 2013;Rocha-Filho & Garófalo, 2013) and observed in the present study, species richness showed temporal variation throughout the year, with the highest values being observed during the rainiest months. The variation in species composition and species richness here reported occurred by the presence of males from six species which were sampled only during the rainiest months.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…In particular, the assembly of bee pollinator communities is strongly influenced by climatic factors as well as variation in food resource availability, which in turn also fluctuates in response to climatic variables (Ramirez et al, 2015). As reported by some authors (Rebêlo & Garófalo, 1991;Silveira et al, 2011;Andrade-Silva et al, 2012;Viotti et al, 2013;Rocha-Filho & Garófalo, 2013) and observed in the present study, species richness showed temporal variation throughout the year, with the highest values being observed during the rainiest months. The variation in species composition and species richness here reported occurred by the presence of males from six species which were sampled only during the rainiest months.…”
Section: Discussionsupporting
confidence: 89%
“…These differences occur mainly due to the presence or absence of species usually represented by few males and by changes in the relative frequencies of each species in each community, as emphasized by Knoll and Penatti (2012). An example is the data reported by Viotti et al (2013) showing Eg. leucotricha, usually represented by few males, as dominant species in a community of high-altitude rocky fields.…”
Section: Resultsmentioning
confidence: 97%
“…The results of the present study, plus those obtained by Viotti et al (2013), Justino and Augusto (2012) Faria and Silveira (2011), Alvarenga et al 2007 andFaria (2004), in other areas of savanna (Cerrado) in Minas Gerais state, revealed a total of 16 orchid bee species for this region. So far there is no list for the orchid bee fauna in the Cerrado of Minas Gerais.…”
Section: Discussionsupporting
confidence: 73%
“…The species richness in Parque do Rio Preto is higher to those found in other inventories carried out in the Cerrado domain (e.g Nemésio & Faria, 2004;Alvarenga et al, 2007;Justino & Augusto, 2010;Faria & Silveira, 2011;Viotti et al, 2013) and in fragments of the semideciduous "low mountain rain forest", at elevations of 300-900 m, in the Atlantic forest domain (Rebêlo & Garófalo, 1997;Sofia & Suzuki, 2004;Nemésio & Silveira, 2010;Silveira et al, 2011;Ferreira et al, 2013). These forests are characterized by relatively open canopy, 15-25 m tall, and occur under climates with two well defined seasons, rainy and dry.…”
Section: Discussioncontrasting
confidence: 58%
See 1 more Smart Citation